Performance of infiltration wells in commercial building along the Kaliurang Road, Yogyakarta, between km 12 – 13 in 2017 - Sri Amini Yuni Astuti (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2024)
Previous studies have shown that incorporating infiltration wells into drainage systems can significantly reduce surface runoff. However, the actual effectiveness of these wells in absorbing rainfall remains uncertain. This article evaluates the performance of infiltration wells installed at commercial buildings along Kaliurang Road (km 12–13) in 2017. Precipitation data was collected from the nearest weather stations: Kemput, Beran, and Bronggang. The design of the infiltration wells followed the Sunjoto technique, utilizing rainfall data from 2001 to 2020 to determine the rainfall intensity for a 5-year return period. To assess the wells' efficiency, daily rainfall data was converted to hourly data using Tadashi Tanimoto's method. The flow rate from rainfall on the roof was compared with the capacity of the infiltration wells. In 2017, the wells' capacity exceeded the flow rate on 363 out of 365 days, demonstrating an exceptionally high-performance rate of 99.45%. On September 28 and November 28, 2017, however, the wells were unable to handle the rainfall due to insufficient capacity.